2020
DOI: 10.1002/cssc.201903578
|View full text |Cite
|
Sign up to set email alerts
|

Pairing Cross‐Linked Polyviologen with Aromatic Amine Host Structure for Anion Shuttle Rechargeable Batteries

Abstract: Scheme1.Expected electrochemical reactionsofM gDAnTand theoretical specific capacities based on the molar massofM gDAnTfor an overall two-electron process.Scheme3.a) Synthesisofp oly(tripyridoniomesytylene) dibromide (c-PVBr 2 ). b) Synthesisofp oly(tripyridoniomesytylene) dihexafluorophosphate by anionic metathesis (c-PV(PF 6 ) 2 ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 31 publications
6
25
0
Order By: Relevance
“…The first example in bulky solid phase for non-aqueous batteries was reported by Yao and co-workers, [257] where poly (1,1'-pentyl-4,4'-bipyridinium dihexafluorophosphate) (denoted [PBPy](PF 6 ) 2 ) was prepared and the electrochemical properties evaluated in n-Bu 4 N•PF 6 /PC electrolyte system (Figure 12b). The polymer displayed excellent reversible extraction/uptake of [258] Copyright 2020, John Wiley and Sons. c) Ionic groups as an adopted strategy to reduce the solubility, voltage profile of (Li 2 )[diacetate-V](ClO 4 ) 2 cycled versus Li + /Li (Reproduced with permission.…”
Section: Viologen Derivativesmentioning
confidence: 99%
See 3 more Smart Citations
“…The first example in bulky solid phase for non-aqueous batteries was reported by Yao and co-workers, [257] where poly (1,1'-pentyl-4,4'-bipyridinium dihexafluorophosphate) (denoted [PBPy](PF 6 ) 2 ) was prepared and the electrochemical properties evaluated in n-Bu 4 N•PF 6 /PC electrolyte system (Figure 12b). The polymer displayed excellent reversible extraction/uptake of [258] Copyright 2020, John Wiley and Sons. c) Ionic groups as an adopted strategy to reduce the solubility, voltage profile of (Li 2 )[diacetate-V](ClO 4 ) 2 cycled versus Li + /Li (Reproduced with permission.…”
Section: Viologen Derivativesmentioning
confidence: 99%
“…The authors ascribed this capacity decay to the solubility of the polymer in the electrolyte, given the low polymerization degree. Additionally, Cadiou et al [258] reported about cross-linked polymerization as an alternative way to lower the dissolution and shuttle issues, by designing a cross-linked polyviologen ([c-PV](ClO 4 ) 2 ) (Figure 12b). The polymer was found to undergo two redox processes at 2.5 and 2.1 V versus Li + /Li, and deliver its theoretical capacity of 88 mAh g −1 (considered as of 2 ClO 4− /e − ).…”
Section: Pfmentioning
confidence: 99%
See 2 more Smart Citations
“…8 In order to avoid the use of an ion-selective membrane and solve the dissolution issue, the employment of polymerized viologens has been demonstrated an effective approach 6,12 For example, a cross-linked ployviologon cathode material coupled with a PF 6 − anion showed excellent chemical and electrochemical stability in the organic liquid electrolyte. 13 the polyxylylviologen chloride (PXVCl 2 ) with abundant chloride ions is first developed as an organic chloride-ion storage electrode material for CIBs. The as-prepared PXVCl 2 electrode delivers an enhanced reversible chloride-ion storage capacity compared to the previously reported conducting polymer electrodes.…”
Section: ■ Introductionmentioning
confidence: 99%